2011
DOI: 10.1111/j.1742-481x.2011.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of vacuum-assisted closure (VAC™) in high-energy complicated perineal injuries: analysis of nine cases

Abstract: Our study reviewed nine patients who were treated with the VAC™ Abdominal Dressing System after suffering pelvic fractures and soft tissue loss after high-energy pelvic trauma. Between March 2008 and August 2009, our clinic treated nine patients with complicated perineal injuries from high-energy pelvic trauma with multiple irrigation and debridement procedures and broad-spectrum antibiotics. Protective ostomies were created for all nine patients. Required interventions were made for associated injuries, and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
1
14
0
4
Order By: Relevance
“…NPWT has been reported to increase the formation of granulation tissue on the wound surface (resulting in improved microperfusion), increase partial oxygen pressure in the tissue and reduce bacterial colonisation . Our earlier study , and also the study by Schaffzin et al , demonstrated that at the end of NPWT, wound care was facilitated and healing was accelerated. These advantages led to earlier wound closure, early skin grafting and earlier hospital discharge .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…NPWT has been reported to increase the formation of granulation tissue on the wound surface (resulting in improved microperfusion), increase partial oxygen pressure in the tissue and reduce bacterial colonisation . Our earlier study , and also the study by Schaffzin et al , demonstrated that at the end of NPWT, wound care was facilitated and healing was accelerated. These advantages led to earlier wound closure, early skin grafting and earlier hospital discharge .…”
Section: Discussionsupporting
confidence: 51%
“…A mine explosion causes a blast wave or ‘blast overpressure’, which is a sudden increase in air pressure over normal atmospheric pressure . Acute traumatic injuries are expected as a result of the blast effect of explosions; however, late visceral injuries and necrosis may also occur as a result of vascular endothelial injuries . Blast injuries cause decreased microcirculation, which can result in a great deal of necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, negative pressure wound closure systems have been widely used for injuries in the perineal region. [5][6][7][8][9][10] The clinical application of NPWT with the VSD has proved to be a very efficient closure technique for our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, early radical debridement and provisional negative pressure wound therapy (NPWT) coverage is widely acknowledged as a reliable approach for the protection of large perineal wounds to prevent infection, stimulate granulation tissue formation, and reduce the area requiring flap coverage, thus improving the success of any subsequent surgery and reducing postoperative complications. [8][9][10] A reliable and clinically relevant classification system for open pelvic fracture is of great importance for clinical care and future research. Such a system provides an effective means of combining similar injuries, distinguishing patterns, and stratifying injury severity.…”
mentioning
confidence: 99%
“…nötrofil akümülasyonuna ve anjiogenesise neden olacak olan IL-8 ve vasküler endotelyal büyüme faktörü- nün lokal artışını sağlar (23,24) . Enfeksiyon nedeniyle o bölgede oluşan enflamatuvar sitokinlerin, proteolitik enzimlerin de sistemik dolaşıma katılmadan ortamdan uzaklaştırılmasını sağlaması da üstün diğer bir özelliğidir (25)(26)(27)(28) .…”
Section: Açik Batin Yöneti̇mi̇unclassified